O wrażliwość społeczną i tolerancję. Wartości wychowawcze w twórczości Haliny Górskiej - Uljasz, Adrian (Przegląd Nauk Historycznych, 2013)
Literary works written for children and social engagement of a Polish writer and educationalist of the interwar period, Halina Górska (1898–1942), made a significant contribution to the Polish literature and ideological thinking. Her literary output deserves broader attention of cultural historians, literary scholars, educationalists, bibliologists and publishers, as it is permeated with constantly relevant educational values. Attitudes promoted by the writer included social sensitivity and tolerance of ethnic differences. Political and social ideas of the Polish left wing party, as well as the Christian tradition had fundamental importance in shaping of her worldview. The paper discusses educational values instilled in Górska’s works, using three books for children and youth first released in 1930’s: a tale O księciu Gotfrydzie rycerzu gwiazdy wigilijnej (A Tale about Gotfryd, Knight of the Christmas Star) and novels Nad czarną wodą (Upon black water), Chłopcy z ulic miasta (Boys of city streets) and Druga brama (The other gate).